COMPARISON OF VENTILATION EFFICACY BETWEEN LMA GASTRO AIRWAY AND ENDOTRACHEAL INTUBATION IN ENDOSCOPIC RETROGRADE CHOLANGIOPANCREATOGRAPHY (Vietnam Journal of Community Medicine, 2026)
Objective: To compare ventilation efficacy between laryngeal gastric mask gastro airway and endotracheal intubation in endoscopic retrograde cholangiopancreatography.Subjects and methods: Randomized controlled trial of 60 patients randomized into two groups: group I (endotracheal intubation) and group II (laryngeal gastric mask gastro airway). Outcome primary: airway insertion time, tidal volume, air leakage, peak airway pressure (Ppeak), and SpO₂ were compared at baseline, immediately post-insertion, pre-lateral positioning, 1 minute and 5 minutes post-lateral positioning, end of surgery, pre-extubation, and 1 minute, 5 minutes, and 10 minutes post-extubation.Results: Laryngeal gastric mask gastro airway insertion time was significantly faster than endotracheal intubation (25,47 ± 5,05 seconds vs 48,53 ± 7,21 seconds, p < 0.01). SpO₂, EtCO₂, and tidal volume remained within normal limits in both groups, with comparable air leak rates < 10%. Peak airway pressure was within normal range and significantly lower in the group II compared to the group I (p < 0,05).Conclusion: Laryngeal gastric mask gastro airway is a suitable and better alternative to endotracheal tube as it allows adequate ventilation efficacy in endoscopic retrograde cholangiopancreatography.
Keywords: Laryngeal mask airway, endotracheal intubation, ventilation efficiency, endoscopic retrograde cholangiopancreatography.